Development of Articulate Storyline-Based IPAS Multimedia to Improve Learning Outcomes among Third-Grade Elementary Students - Utami, Apriliana Prili; Isdaryanti, Barokah (Jurnal Paedagogy, 2026)
This study aims to develop and evaluate Articulate Storyline-based multimedia to improve learning outcomes in Natural and Social Sciences (IPAS), specifically on the topic of “Diversity of Landforms in Indonesia” for third-grade students at Bringin 01 Public Elementary School, Semarang. The study employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. Data were collected through interviews, questionnaires, and learning outcome tests. The data analysis techniques included normality testing, paired-sample t-tests, and normalized gain (N-gain) analysis. The multimedia product was developed using Articulate Storyline software and subsequently validated by media experts and subject matter experts, yielding scores of 93.33% and 90.78%, respectively, which were categorized as highly feasible. Teacher responses reached 95%, while student responses were 89.13%, both of which fell into the very feasible category. The effectiveness test results indicated a significant improvement between pre-test and post-test scores in both small- and large-scale trials (sig. = 0.000 < 0.05). Furthermore, the N-gain analysis showed a high improvement in the small-scale trial (0.7337) and a moderate improvement in the large-scale trial (0.6415). In conclusion, the Articulate Storyline-based IPAS multimedia is valid, practical, and effective in improving students’ learning outcomes in elementary school IPAS subjects.